2013
DOI: 10.1186/1749-8090-8-118
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative hypoxemia in patients undergoing Stanford A aortic dissection surgery

Abstract: BackgroundThe purpose of this study is to identify the risk factors for postoperative hypoxemia in patients with Stanford A aortic dissection surgery and their relation to clinical outcomes.MethodsClinical records of 186 patients with postoperative hypoxemia in Stanford A aortic dissection were analyzed retrospectively. The patients were divided into two groups by postoperative oxygen fraction (PaO2/FiO2):hypoxemia group (N=92) and non-hypoxemia group (N=94).ResultsWe found that the incidence of postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 28 publications
5
58
1
Order By: Relevance
“…These results are similar to those published by others who have shown a variety of associated risk factors for PMV including excessive blood loss, increased age of the patient, time from symptom onset to surgery, low preoperative oxygenation, and prolonged circulatory arrest time. 11,12 The authors of the current report demonstrated a number of interesting associated risk factors including increased blood products transfused, serum lactate at conclusion of surgery, preoperative platelet count, and the oxygenation index at conclusion of surgery. They also performed propensity matching analysis, which limited the size significantly, finding 25 matched pairs, demonstrating increased mortality in the PMV group associated with excessive transfusion.…”
mentioning
confidence: 67%
“…These results are similar to those published by others who have shown a variety of associated risk factors for PMV including excessive blood loss, increased age of the patient, time from symptom onset to surgery, low preoperative oxygenation, and prolonged circulatory arrest time. 11,12 The authors of the current report demonstrated a number of interesting associated risk factors including increased blood products transfused, serum lactate at conclusion of surgery, preoperative platelet count, and the oxygenation index at conclusion of surgery. They also performed propensity matching analysis, which limited the size significantly, finding 25 matched pairs, demonstrating increased mortality in the PMV group associated with excessive transfusion.…”
mentioning
confidence: 67%
“…Wang et al [17], in a retrospective study, analyzed data on risk factors for hypoxemia (defined as PaO 2 /FiO 2 <200) after Stanford A aortic dissection. Postoperative hypoxemia was present in 49.5% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The method of pulmonary static inflation with 50% xenon during CBP is easy to operate and effectively attenuates decreased OI and increased RI at the end of surgery, which may save more lives.…”
Section: Discussionmentioning
confidence: 99%